2014
DOI: 10.5433/1679-0359.2014v35n4suplp2617
|View full text |Cite
|
Sign up to set email alerts
|

Características de carcaça e qualidade da carne de novilhos terminados em pastagem de aveia branca

Abstract: ResumoObjetivou-se com este estudo avaliar as características de carcaça e qualidade da carne de novilhos terminados exclusivamente em pastagem de aveia branca (Avena sativa L.) ou consorciada com ervilhaca (Vica sativa) ou associada à suplementação energética a base de grão de milho triturado. Foram utilizados 18 novilhos castrados, cruzados das raças 1/4 Marchigiana -1/4 Aberdeen Angus -2/4 Nelore, com peso vivo e idade média inicial de aproximadamente 360 kg e 19 meses, respectivamente. Durante 72 dias os n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
2
1
0
1
Order By: Relevance
“…Significant differences were not found for carcass measurement traits. This corroborates a previous study (Hirai et al, 2014), which found no differences in carcass measurement traits between animals with the same genetic patterns and similar ages at slaughtering. When standardized for weight, carcass measurements are a straightforward indicator of carcass conformation (Campion et al, 2009), which may explain the similarity in carcass conformation characteristics between treatments.…”
Section: Resultssupporting
confidence: 92%
“…Significant differences were not found for carcass measurement traits. This corroborates a previous study (Hirai et al, 2014), which found no differences in carcass measurement traits between animals with the same genetic patterns and similar ages at slaughtering. When standardized for weight, carcass measurements are a straightforward indicator of carcass conformation (Campion et al, 2009), which may explain the similarity in carcass conformation characteristics between treatments.…”
Section: Resultssupporting
confidence: 92%
“…Similar values of TEX and COR were found by Hirai et al (2014), who evaluated steers finished on pasture. Lower values for color were found, regardless of the treatments, with a mean value of 3.54.…”
Section: Con 10butsupporting
confidence: 61%
“…However, PD and PT, amounted, on average, to 38.9 and 59.14%, respectively, of the hot carcass weight. Hirai et al (2014) reported values of 36.42 and 63.58%, for the forequarter and hindquarter yields, respectively.…”
Section: Con 10butmentioning
confidence: 99%
“…Nesse sentido, a partir de uma ligeira redução da fração fibrosa da aveia fertilizada, é possível sugerir o maior percentual de NDT para o tratamento com o uso de N em relação aos consórcios com trevobranco e trevo-vermelho. Os valores encontrados neste trabalho são superiores aos reportados por Hirai et al (2014), de 50,49% NDT, em uma pastagem de aveia e ervilhaca. Porém, são inferiores ao reportado por Hanisch et al (2015), de 70%, para o consórcio de azevém e ervilhaca.…”
Section: Resultsunclassified